Attribution of intentions and creative musical interaction during jazz improvisation: the second person perspective in music cognition - Marchiano, María (2023)
Aims: To classify the mutual attributions of intentions to the other musicians’ mental states in episodes of second person interaction during online jazz improvisation. To analyze the links between the mental attributions of intentions made and the creative musical exchanges.